2005
DOI: 10.1123/jpah.2.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Participation in Physical Activity for Adolescent Girls: A Systematic Review of Recent Literature

Abstract: Background:Many adolescent girls have low levels of physical activity and participation declines with age. This review identifies recent correlates of physical activity in adolescent girls.Methods:Systematic review of papers published 1999 to mid-2003. Papers (k = 51) reporting a measure of physical activity and at least one potential correlate of physical activity in adolescent girls were analyzed.Results:Demographics related to physical activity were female gender (–), non-white ethnicity (–), age (–), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
243
6
21

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(296 citation statements)
references
References 64 publications
26
243
6
21
Order By: Relevance
“…Findings here are consistent with previous research showing that early pubertal maturation is associated with negative psychological well-being among girls (Graber et al, 1997) and that psychological well-being (Biddle, Whitehead, O'Donovan, & Nevill, 2005) and enjoyment of physical activity predict physical activity among youth. Moreover, findings from this study build on previous research.…”
Section: Discussionsupporting
confidence: 82%
“…Findings here are consistent with previous research showing that early pubertal maturation is associated with negative psychological well-being among girls (Graber et al, 1997) and that psychological well-being (Biddle, Whitehead, O'Donovan, & Nevill, 2005) and enjoyment of physical activity predict physical activity among youth. Moreover, findings from this study build on previous research.…”
Section: Discussionsupporting
confidence: 82%
“…We also found that social support influenced girls’ task self-efficacy, or confidence in their abilities to be physically active. These findings suggest that social support is an important contributor of girls’ self-efficacy for PA, which has been consistently associated with girls’ PA levels (Biddle, Whitehead, O’Donovan, & Nevill, 2005; Craggs, Corder, van Sluijs, & Griffin, 2011). Increased self-efficacy from social support was linked to increases in motivation to be physically active.…”
Section: Discussionmentioning
confidence: 84%
“…This study purposely targeted girls who were active and the findings reflect different domains of PA, however, the majority of the participants were involved in organized sports. Whilst previous research has highlighted that being involved in organized sport is a strong determinant of PA levels in adolescent girls (Biddle et al, 2005), it is possible that girls who are not involved in organized sport may have different responses to social support than inactive girls. Intervention studies are therefore warranted to test potential social support intervention strategies identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health benefits of physical activity may result from increases in social support and a sense of mastery as well as changes in noradrenaline and neurotransmitters such as dopamine and serotonin [1]. Recent reviews of the literature, however, indicate that empirical support for the link between participation in physical activity and psychosocial well-being is infrequent and inconclusive [2][3][4][5]. With this in mind, this study assesses the longitudinal association between physical activity and global self-esteem in a sample of adolescent girls, a population at risk for depression and low selfesteem [6][7][8].…”
mentioning
confidence: 99%
“…Higher levels of self-esteem are associated with increased self-efficacy, body image, and leadership, and reduced levels of depression and anxiety [5,9]. As outlined in recent reviews [2,5,10], few studies have examined the link between physical activity and self-esteem among adolescent girls, and no studies have tested the direction of this association. Given the low rates of physical activity participation in this population [11], these are important questions to address.…”
mentioning
confidence: 99%